Factors Associated with Late Initiation of Highly Active Antiretroviral Therapy among Young HIV-Positive Men and Women Aged 18 to 29 Years in Canada. (January 2014) - Palmer, Alexis K.; Cescon, Angela; Chan, Keith; Cooper, Curtis; Raboud, Janet M.; Miller, Caroline L.; Burchell, Ann N.; Klein, Marina B.; Machouf, Nima; Montaner, Julio S. G.; Tsoukas, Chris; Hogg, Robert S.; et al.
Initiating highly active antiretroviral therapy (HAART) with low CD4 counts or AIDS-defining illnesses (ADIs) increases risk of treatment failure and death. We examined factors associated with late initiation among 18- to 29-year-olds within the Canadian Observational Cohort (CANOC) collaboration, a multi-site study of HIV-positive persons who initiated HAART after 2000. Late initiation was defined as beginning HAART with a CD4 count <200 cells/mm 3 and/or having a baseline ADI. Multivariable logistic regression was used to identify independent correlates of late initiation. In total, 1026 individuals (422 from British Columbia, 400 from Ontario, and 204 from Quebec) met our age criteria. At HAART initiation, median age was 27 years (interquartile range, 24, 28 years). A total of 412 individuals (40%) identified as late initiators. Late initiation was associated with female gender, age >25 years at initiation, initiating treatment in earlier years, and having higher baseline viral load. The high number of young adults in our cohort starting HAART late indicates important target populations for specialized services, increased testing, and linkages to care.